Methylation analysis of Klebsiella pneumoniae from Portuguese hospitals - Spadar, Anton; Perdigão, João; Phelan, Jody; Charleston, James; Modesto, Ana; Elias, Rita; Sessions, Paola Florez de; Hibberd, Martin L.; Campino, Susana; Duarte, Aida; Clark, Taane G. (Springer Nature, 2021)
Klebsiella pneumoniae is an important nosocomial infectious agent with a high antimicrobial resistance (AMR) burden. The application of long read sequencing technologies is providing insights into bacterial chromosomal and putative extra-chromosomal genetic elements (PEGEs) associated with AMR, but also epigenetic DNA methylation, which is thought to play a role in cleavage of foreign DNA and expression regulation. Here, we apply the PacBio sequencing platform to eight Portuguese hospital isolates, including one carbapenemase producing isolate, to identify methylation motifs. The resulting assembled chromosomes were between 5.2 and 5.5Mbp in length, and twenty-six PEGEs were found. Four of our eight samples carry blaCTX-M-15, a dominant Extended Spectrum Beta Lactamase in Europe. We identified methylation motifs that control Restriction–Modification systems, including GATC of the DNA adenine methylase (Dam), which methylates N6-methyladenine (m6A) across all our K. pneumoniae assemblies. There was a consistent lack of methylation by Dam of the GATC motif downstream of two genes: fosA, a locus associated with low level fosfomycin resistance, and tnpB transposase on IncFIB(K) plasmids. Overall, we have constructed eight high quality reference genomes of K. pneumoniae, with insights into horizontal gene transfer and methylation m6A motifs.
Keywords: Klebsiella pneumoniae; Methylation; Hospitals; Portugal